Retail Efficiency And Productivity Enhancement Through Ergonomic Design - Ooi, Boon Jiet; Majid, Ahmad Zuhairi Abdul (2014)
Ergonomic design is one of the primary keys in improving the retail business process efficiency and productivity. Design concept & methods applied in the following research are applied on back-end processes of retail management and not standard B2C (business to consumers) environment. Major parts of the research are applied on live-project and hence the results of this research are highly dependent on thousands of users’ feedback and critiques.The hypothesis of our designer is proved, that through controlled design environment and actual customers’ feedbacks, an enhanced ergonomic design in retail management is able to increase the user to perform daily retail management task significantly faster. Human made error were greatly reduced and precision of the expected results were a lot higher. Not to mention training hours for new user to adapt to the new design are decreased from 12 hours to less than 3 hours (An average of 300% decrease on training hours). These design methods in ergonomic design are hence proven to enhanced retail efficiency and productivity with immediate and significant effects